Relative Sensitivity of Conventional and PCR-based Approaches for the Detection of Clinical Methicillin-resistant Staphylococcus aureus - Sidiq, Avin Salih; Ameen, Sirwan Muhsin Muhammed (Sulaimani Journal for Pure and Applied Sciences, 2019)
The aim of the present study was to investigate the use of PCR and disk diffusion methods in determination of methicillin-resistant Staphylococcus aureus (MRSA) strains and compare their accuracy and specificity. For this purpose a total of 150 clinical isolates obtained from burn patients were investigated; of these 55 (36.6 %) were identified as S. aureus by conventional and Vitek® 2 system. All isolates were subjected to 30 μg cefoxitin to identify MRSA isolates. Besides, PCR was utilized for molecular analysis. Among the results of disk diffusion methods in our study, the prevalence of MRSA was 92.7% and MSSA was 7.3% with the sensitivity and specificity of 92.15 % and 75 % respectively. Whereas, 87.3 % of S. aureus isolates were mecA positive and 12.7% were mecA negative in PCR assay. Our finding showed that the PCR is more accurate and allowed early and rapid identification of methicillin-resistant S.aureus
Keywords: MRSA; cefoxitin; polymerase chain reaction; Saureus